Urgensi Manajemen Konflik dalam Meningkatkan Kinerja Organisasi - Abdur Rozaq; Yova Hamdani; Eka Putrilhiya; Nur Liani; Mu’allimin Mu’allimin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Conflict management is a crucial element in organizational management aimed at effectively improving performance. Poorly managed conflicts can lead to decreased productivity, interpersonal tension, and disruptions in achieving organizational goals. However, when managed with the right strategies, conflicts can act as catalysts for innovation, collaboration, and process improvement. This study uses a literature review method to analyze theories and empirical findings on the urgency of conflict management in organizations. The results show that strategies such as open communication, mediation, and routine evaluation play a significant role in transforming conflicts into opportunities. By implementing effective conflict management, organizations can create a harmonious work environment, enhance collaboration among members, and optimize goal achievement.